Bone marrow donor‐related variables associated with harvest outcome in HLA‐haploidentical transplantation with postinfusion cyclophosphamide. Issue 1 (25th February 2016) - Rimondo, A.; Bramanti, S.; Crocchiolo, R.; Giordano, L.; Sarina, B.; Morabito, L.; Perotti, C.; Timofeeva, I.; Capizzuto, R.; Santoro, A.; Castagna, L.
Abstract : Background and objectives: Several transplantation outcomes have been shown to be associated with the infused bone marrow cell dose/kg of the recipient's body weight. The donor bone marrow density is directly related to the infused cell dose. The aim of the present study was to identify donor‐related variables that are associated with high donor bone marrow density. Materials and methods: We retrospectively analysed the predictive factors of high marrow density in 65 consecutive HLA‐haploidentical bone marrow donors harvested at our centre between 2009 and 2013. Results: Body mass index (BMI) and peripheral white blood cell (WBC) count were directly associated with bone marrow density (regression coefficient β = 5·33 and β = 2·93, respectively; P < 0·01). The likelihood of obtaining a collection with a high density was first predicted using BMI (BMI ≥30, mean density = 25·8 TNC/ml × 10 6 ). Second, donors with a BMI <30 were split into two groups according to peripheral WBC count (WBC <8 × 10 3 /mm 3 : mean density = 18·4 TNC/ml × 10 6 ; WBC ≥8 × 10 3 /mm 3 : mean density = 23·1 TNC/ml × 10 6 ). We also observed that the density of the first collected bag directly correlated with the overall density ( R 2 = 0·69, P < 0·01). Conclusion: The donor‐related features BMI and WBC count affect the cell quantity obtainable with the harvest and should be taken into account when choosing the donor.